2020
DOI: 10.1155/2020/8626495
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ganglion Cell Complex and Peripapillary Retinal Nerve Fiber Layer after Femtosecond Laser-Assisted Cataract Surgery Compared to Manual Phacoemulsification in Patients Receiving a Trifocal Intraocular Lens

Abstract: Introduction. During femtosecond laser-assisted cataract surgery (FLACS), there is a significant increase in intraocular pressure, which might lead to ganglion cell damage. We aimed to determine whether there were differences in the changes produced in the ganglion cell complex (GCC) and peripapillary retinal nerve fiber layer (pRNFL) thickness, as evaluated with optical coherence tomography (OCT), between phacoemulsification and FLACS, after implantation of a trifocal intraocular lens (IOL). Methods. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…The sample size of our CPCS group is close to many of the other studies in the literature on the effect of CPCS on pRNFL. 10,[13][14][15][16][17] Moreover, CPCS generated a similar variance of change within the average pRNFL in this study as in the study by Sánchez-Sánchez et al 7 Therefore, there is evidence to support the validity of our CPCS group. Nevertheless, the significant difference in sample size between groups limits the possibility of establishing accurate comparisons.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The sample size of our CPCS group is close to many of the other studies in the literature on the effect of CPCS on pRNFL. 10,[13][14][15][16][17] Moreover, CPCS generated a similar variance of change within the average pRNFL in this study as in the study by Sánchez-Sánchez et al 7 Therefore, there is evidence to support the validity of our CPCS group. Nevertheless, the significant difference in sample size between groups limits the possibility of establishing accurate comparisons.…”
Section: Discussionsupporting
confidence: 87%
“…This observation is compatible with our finding. Like us and as in the previous study, Sánchez-Sánchez et al, 7 via Cirrus HD-OCT showed an increase in average pRNFL thickness, 3 months after FLACS using LenSx laser, and a trifocal IOL implantation, in 74 eyes. Direct comparison with that study is limited by dissimilar OCT devices and IOL types.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The aim of this study was to evaluate and compare the changes in BMO-MRW, RNFL, and MT one month and six months after cataract surgery, in CCS and FLACS. Some studies have shown that FLACS does not lead to more macular thickening than CCS [ 12 16 ], but there is a paucity of evidence regarding the effects of CCS and FLACS on the ONH [ 23 , 24 ]. In the present study, the postoperative behaviour of BMO-MRW, RNFL, and MT was very similar in both groups.…”
Section: Discussionmentioning
confidence: 99%